Potential of knowledge management as antecedence of sustainable supply chain management practices - Abd Rahman, Azmawani; Tay, Mee Yean; Abd Aziz, Yuhanis (ExcelingTech Publishers, 2016)
The importance of environmental protection has become topical in general economic development strategies of emerging economies. If sustainable development is desired, business practices along the supply need to consider the environmental protection, social contribution, and economics development. This paper discusses the concept of sustainable supply chain management (SSCM) in business. First, it provides definition of sustainable supply chain from a comprehensive review of the literature. Second, it discusses the factors that have been found to motivate firms to implement SSCM. Finally, it highlights the gaps of knowledge in factors affecting the implementation of SSCM and introduces the role of knowledge management as antecedence of SSCM. This paper offers some insights that are relevant in theory and practice.